Sufism as a Therapy in the Modern Life - Hoerul Umam; Iyad Suryadi (UIN Sunan Gunung Djati Bandung, 2019)
Sufism or Taṣawwuf is an ancient fruit of Islamic civilization, but experienced revitalization in this modern era. His presence was increasingly meaningful when he was able to become an